2016
DOI: 10.1245/s10434-016-5554-z
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Reconstruction in Inflammatory Breast Cancer: Challenging Current Care

Abstract: Performing IR with mastectomy for IBC is associated with increased complications, but is not associated with decreased survival or increased recurrence in selected patients. IR in selected IBC patients can facilitate successful breast reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Simpson et al reported their institutional experience with breast reconstruction in 60 patients with stage III IBC. Sixteen (27%) underwent immediate reconstruction: 81%—tissue expander placement and 19%—autologous tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Simpson et al reported their institutional experience with breast reconstruction in 60 patients with stage III IBC. Sixteen (27%) underwent immediate reconstruction: 81%—tissue expander placement and 19%—autologous tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Simpson et al also found that immediate reconstruction was not associated with a delay in initiating RT. The patients who underwent immediate reconstruction began RT after a median of 52.5 days post‐MRM, which was not statistically significant from the time of initiating RT among those with delayed reconstruction or no reconstruction (45 days and 42 days, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few single-institution studies and a SEER-Medicare database study have suggested that performing IBR for patients with IBC does not negatively impact survival [49,[54][55][56]. Chin et al compared 23 IBC patients who underwent mostly autologous reconstruction (14 in the IBR setting) to nonreconstructed historical controls and found no difference in disease-free or OS [54].…”
Section: Safety Of Immediate Breast Reconstructionmentioning
confidence: 99%
“…,16,17 Chin et al3 reported no difference in disease-free or overall survival when comparing 22 IBC patients to nonreconstructed historical controls. The median disease-free and overall survival rates were 19 and 22 months, respectively.…”
mentioning
confidence: 99%